Catholic and Quaker Attitudes to Work, Rest, and Play in Seventeenth- and Eighteenth-Century England - Mullett, Michael A. (Studies in church history, 2002)
Since its publication in 1904-5, Max Weber’s The Protestant Ethic and the Spirit of Capitalism has provided a paradigm for assessments of the attitudes to the profitable use of time among different branches of Christianity, emphasising the sanctification of work and thrifty care for time allegedly found in pronouncedly Protestant religious groups. This paper tests further assumptions made by Weber and his school by considering attitudes espoused within the two religious groups in early modern England which are often taken to epitomize the stereotypical extremes of Weberian hypotheses: on the one hand the Catholics, on the other the Quakers.